FcRn Antagonism Leads to a Decrease of Desmoglein-Specific B Cells: Secondary Analysis of a Phase 2 Study of Efgartigimod in Pemphigus Vulgaris and Pemphigus Foliaceus - Maho-Vaillant, Maud; Sips, Magdalena; Golinski, Marie-Laure; Vidarsson, Gestur; Goebeler, Matthias; Stoevesandt, Johanna; Bata-Csörgő, Zsuzsanna; Balbino, Bianca; Verheesen, Peter; Joly, Pascal; Hertl, Michael; Calbo, Sébastien (Frontiers in Immunology, 2022)
Background: Immunoglobulin G (IgG) levels are maintained by the IgG-recycling neonatal Fc-receptor (FcRn). Pemphigus vulgaris and pemphigus foliaceus are debilitating autoimmune disorders triggered by IgG autoantibodies against mucosal and epidermal desmogleins. Recently, a phase 2 clinical trial (NCT03334058; https://clinicaltrials.gov/NCT03334058) was completed in participants with pemphigus using efgartigimod, an FcRn inhibitor, in combination with prednisone. Efgartigimod demonstrated an early effect on disease activity, and was well tolerated. In addition to the safety and efficacy assessment, clinical trials present an opportunity to gain more insights on the mechanism of disease, the mode of action of treatment, and potential for corticosteroid-sparing activity. Objective: The aim of our study was to assess the impact of FcRn antagonism by efgartigimod on immunological parameters known to be directly involved in pemphigus pathology, such as cellular and serological responses. Methods: We investigated total and antigen-specific IgG subclass level kinetics during and after treatment, assessed antigen-specific B cell responses, followed T- and B-cell immunophenotypes, and analyzed how different immunophenotypes link with clinical response. Results: Treatment resulted in reduction of total IgG as well as autoreactive IgG antibody levels. Surprisingly, unlike total IgG and vaccine- or natural-infection-elicited IgG, which returned to baseline levels after stopping efgartigimod treatment, autoreactive antibody levels remained low in several study participants. Efgartigimod showed no effect on total leukocytes, neutrophils, monocytes, or lymphocytes in patients treated with extended efgartigimod therapy. Intriguingly, antigen-specific analyses revealed a loss of desmoglein-specific B cells in several participants responding to efgartigimod, in line with prolonged reduction of pathogenic IgG levels. Conclusions: Efgartigimod treatment of participants with pemphigus improved their conditions and exerted an immunomodulatory effect beyond the blockade of IgG recycling. Further studies in larger populations with an appropriate placebo control are needed to confirm these potentially important observations to establish long-term clinical responses in autoimmune diseases.